Medfly Ceratitis capitata as Potential Vector for Fire Blight Pathogen Erwinia amylovora: Survival and Transmission - Ordax, Mónica; Piquer-Salcedo, Jaime E.; Santander, Ricardo D.; Sabater-Munoz, Beatriz; Biosca, Elena G.; López, María M.; Marco-Noales, Ester (2017)
Monitoring the ability of bacterial plant pathogens to survive in insects is required for elucidating unknown aspects of their epidemiology and for designing appropriate control strategies. Erwinia amylovora is a plant pathogenic bacterium that causes fire blight, a devastating disease in apple and pear commercial orchards. Studies on fire blight spread by insects have mainly focused on pollinating agents, such as honeybees. However, the Mediterranean fruit fly (medfly) Ceratitis capitata (Diptera: Tephritidae), one of the most damaging fruit pests worldwide, is also common in pome fruit orchards. The main objective of the study was to investigate whether E. amylovora can survive and be transmitted by the medfly. Our experimental results show: i) E. amylovora can survive for at least 8 days inside the digestive tract of the medfly and until 28 days on its external surface, and ii) medflies are able to transmit the bacteria from inoculated apples to both detached shoots and pear plants, being the pathogen recovered from lesions in both cases. This is the first report on E. amylovora internalization and survival in/on C. capitata, as well as the experimental transmission of the fire blight pathogen by this insect. Our results suggest that medfly can act as a potential vector for E. amylovora, and expand our knowledge on the possible role of these and other insects in its life cycle.